Pengaruh Kecerdasan Spiritual Terhadap Kinerja Auditor Pada Badan Pemeriksa Keuangan Republik Indonesia (BPK-RI) Perwakilan Provinsi Sulawesi Selatan - Sambo, Eva Marin; Rahayu, Andi Juliana (Insan Cita Bongaya Research Journal, 2023)
Abstract: This study aims to determine the influence of Spiritual Intelligence on Auditor Performance at the Audit Board of the Republic of Indonesia Representative of South Sulawesi Province. The sampling technique uses the Nonprobability Sampling technique (convienence sampling) so that a sample of 37 respondents was obtained. Data analysis methods for hypothesis testing are performed using simple regression tests and t tests. The results of this study show that spiritual intelligence has a positive and significant effect on auditor performance. The better the spiritual intelligence, the better the auditor's performance. The r square value obtained has a moderate magnitude, this is because there are still some respondents who answer with hesitant answers and disagree on some statements.